Karnofsky performance status predicts outcomes in candidates for simultaneous liver‐kidney transplant. Issue 2 (29th December 2020) - Shamseddeen, Hani; Pike, Francis; Ghabril, Marwan; Patidar, Kavish R.; Desai, Archita P.; Nephew, Lauren; Anderson, Melissa; Kubal, Chandrashekhar; Chalasani, Naga; Orman, Eric S.
Abstract: Karnofsky performance status (KPS), a measure of physical frailty, predicts pre‐transplant and post‐transplant outcomes in liver transplantation, but has not been assessed in simultaneous liver–kidney transplantation (SLKT). We examined the association between KPS and outcomes in SLKT waitlist registrants and recipients (2005‐2018) in the UNOS database. KPS was categorized into A (able to work), B (able to provide self‐care), and C (unable to provide self‐care). Cox regression and competing risk analysis were used to assess the association between KPS groups and outcomes. A total of 10, 785 patients were waitlisted (KPS: 19% A, 46% B, 35% C), and 5, 516 underwent SLKT (12% A, 36% B, 52% C). One‐year waitlist mortality was 17%, 22%, and 32% for KPS A, B, and C, respectively. In adjusted competing risk regression, KPS C was associated with increased waitlist mortality (SHR 1.15, 95%CI 1.04‐1.28). One‐year post‐transplant survival was 92%, 91%, and 87% for KPS A, B, and C, respectively. In adjusted Cox regression, KPS C was associated with increased post‐transplant mortality (HR 1.32, 95%CI 1.08‐1.61). It was also associated with increased liver and kidney graft losses and with hospital length of stay. Frailty, as assessed by KPS, is associated with poor outcomes in SLKT pre‐ and post‐transplant.